2001
DOI: 10.1046/j.1365-2508.2001.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of hysteroscopy in diagnosis and treatment of missing intra‐uterine devices

Abstract: Objective To evaluate the efficacy of hysteroscopy for diagnosis and treatment of missing intra‐uterine devices (IUDs). Design A retrospective study of 274 patients. Setting Shanghai Institute of Planned Parenthood Research, Shanghai Jiading District Gynaecological Endoscopy Centre and Shanghai First Maternity and Infant Health Hospital. Subjects 274 patients with missing IUDs, who had previously undergone up to four unsuccessful attempts at IUD removal, were included in our study. Among them, 45 patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There were studies recommending usage of hysteroscopy for embedded or displaced IUCD. A study by Zuan Chong Feng et al mentioned that hysteroscopy with an ultrasound B-scan is of great value not only for precise location but also for its removal under direct vision, particularly in the management of patients with broken and/or embedded IUCD pieces [3]. A study by Dwyer and James revealed that the incidence of difficulties associated with IUCD removal may occur in up to 9% of follow-up visits of women who have been fitted with IUCD [4].…”
Section: Introductionmentioning
confidence: 99%
“…There were studies recommending usage of hysteroscopy for embedded or displaced IUCD. A study by Zuan Chong Feng et al mentioned that hysteroscopy with an ultrasound B-scan is of great value not only for precise location but also for its removal under direct vision, particularly in the management of patients with broken and/or embedded IUCD pieces [3]. A study by Dwyer and James revealed that the incidence of difficulties associated with IUCD removal may occur in up to 9% of follow-up visits of women who have been fitted with IUCD [4].…”
Section: Introductionmentioning
confidence: 99%